Prevalence of multidrug resistant Shigella isolated in Malaysia - Thong, Kwai Lin; Hoe, C.H.; Koh, Y.T.; Yasin, R.M. (Icddr:b, 2002)
Shigellosis, a disease caused by Shigella spp., is endemic in Malaysia. Its low infective dose and ease of spread through person-to-person transmission by the faecal-oral route make this infection difficult to control in outbreak situations. Antimicrobial therapy is recommended for shigellosis because it can shorten the severity and duration of illness, reduce shedding of the organism, and prevent secondary complications and deaths. However, due to the global emergence of drug resistance, the choices of antimicrobial agents for empiric therapy for shigellosis are now limited. Although antimicrobial resistance of Shigella spp. is well-documented in many countries (2-4), there is a lack of such documentation in Malaysia. Hence, the study was undertaken to determine the antimicrobial resistance patterns of the Malaysian strains of Shigella spp. This study, to the best of our knowledge, is the first report on the antimicrobial resistance of Shigella spp. in Malaysia.